Soluble Toll-like receptor 1 family members in the amniotic fluid of women with preterm prelabor rupture of the membranes - Kacerovsky, Marian; Andrys, Ctirad; Drahosova, Marcela; Musilova, Ivana; Hornychova, Helena; Lesko, Daniel; Tosner, Jindrich; Jacobsson, Bo (The journal of maternal-fetal & neonatal medicine, 2012)
OBJECTIVE: To determine soluble Toll-like receptor (sTLR) 1, sTLR2 and sTLR6 concentrations in amniotic fluid (AF) of women with preterm prelabor rupture of membranes (PPROM) and if there is an association with microbial invasion of the amniotic cavity and histological chorioamnionitis (HCA). METHODS: Cross-sectional study was performed. Forty-two women with singleton PPROM pregnancies at a gestational age between 24 + 0 and 36 + 6 weeks were included in the study (twenty-two women with presence of both microbial invasion of the amniotic cavity and HCA, and 20 women without microbial invasion of the amniotic cavity and HCA). Amniocenteses were performed, and the concentrations of sTLRs were determined by sandwich enzyme-linked immunosorbent assays. RESULTS: Women with microbial invasions of the amniotic cavity and HCA (n = 22) had significantly higher median sTLR1, sTLR2 and sTLR6 levels than those without (n = 20). (20.4 ng/mL vs. 0.44 ng/mL; p < 0.0001, 577.6 ng/mL vs. 60.7 ng/mL; p < 0.0001 and 0.44 ng/mL vs. 0.26 ng/mL; p = 0.02, respectively). CONCLUSIONS: Women with microbial invasion of the amniotic cavity and HCA had higher AF sTLR1, 2 and 6 levels.
Keywords: Predictive Value of Tests; Prognosis; Amniotic Fluid; nemoci nedonošenců; Adult; Pregnancy; lidé; Multigene Family; Humans; rozpustnost; morbidita; novorozenec; Solubility; prediktivní hodnota testů; předčasný odtok plodové vody; Young Adult; plodová voda; Fetal Membranes, Premature Rupture; Infant, Premature, Diseases; toll-like receptor 1; průřezové studie; dospělí; mladý dospělý; multigenová rodina; Morbidity; Cross-Sectional Studies; ženské pohlaví; Prenatal Diagnosis; chorioamnionitida; těhotenství; Female; prognóza; Obstetric Labor, Premature; Toll-Like Receptor 1; předčasná porodní činnost; prenatální diagnóza; Infant, Newborn; Chorioamnionitis